PERAN YAYASAN TENDAVISI INDONESIA DALAM MENGATASI KRISIS AIR MELALUI PROGRAM WAKAF SUMUR DI KAMPUNG SITUSIPATAHUNAN DESA BALEENDAH - Fauziah, Riana Damayanti (IKIP Siliwangi, 2021)
Â The background of the research is about phenomenon of situsipatahunan village. People around the situsipatahunan are continuining to suffer from acces poor to water and hygiene. The purpose of research is : (1) To find out the process of well waqf program. (2) To find out the relationship between the well waqf program with the community empowerment process. The type of research is descriptive field research by using qualitative approach. Then the techniques to collect data in research uses interview, observation, and documentation. The research location is in the kampung situsipatahunan rt/rt 03/05 desa Baleendah, kec. Baleendah - kab. Bandung and the subject research are the management of the foundation as a responsible person of well waqf program and the communities who resceive the benefits off well waqf as many as fourty families around the construction of well waqf. Based on the result the activity of well waqf program goes well. The program is carried out by means of sites surveys activities, fundraising and the well waqf execution. The relationship between well waqf and community empowerment is the use off well waqf to increase the economic level of people in Situsipatahunan village.